Social movements in the context of crisis: waste picker organizations as collaborative public partners in the context of the COVID-19 pandemic - Gutberlet, Jutta; Azevedo, Adalberto Mantovani Martiniano de; Morais, Leandro [UNESP]; Bacic, Miguel Juan; Mesquita, Maryellen Silva de (Sage Publications Ltd, 2023)
Social movements are purposeful, organized groups of people addressing the creation and reproduction of inequality, rights and access issues, seeking to transform sectoral policies. In the context of the COVID-19 pandemic, social movements have been acting in articulation with government and private companies and through other actions formulated within their networks, as service deliverers to the poor and vulnerable populations most heavily affected, often filling a gap created by unfulfilled policies. Our research with waste picker organizations in Brazil illustrates how their struggle for recognition has taken action in this context. Academic and government documents, social media and online material (blogs, posts, websites, etc.) and virtual meetings inform this research. We found that multiple actors have contributed to mitigate the urgent needs of waste pickers during the pandemic, but that at the same time, pre-existing challenges in waste management and the lack of wide-ranging social and economic inclusion have been further intensified.
Keywords: Brazil; COVID-19; pandemic; social and solidarity economy; social movements; waste picker organizations